Guided Inquiry Learning with Outdoor Activities Setting to Improve Critical Thinking Ability and Science Process Skills of Elementary School Students (Journal of Primary Education, 2020)
The research aims to analyze the effectiveness of the guided inquiry model with outdoor activities setting on the critical thinking ability and science process skills of students. This is quantitative research applying a quasi-experimental with nonequivalent control group design. The population of this study were all students of SDN Gajah 2 Demak. The subjects of this study were students of class IV A as the control group and class IV B as the experimental group. Students in the experimental group were taught using the guided inquiry model with outdoor activities setting, while the students in the control group were taught using the guided inquiry model. The instruments used to measure the success of this study were essay questions to measure students' critical thinking skills and observation sheets to measure science process skills in the psychomotor domain. The results show that the use of guided inquiry models with outdoor activities setting is effective in developing critical thinking skills and science process skills. There are differences in the average score of critical thinking skills in the experimental and the control group with a significance level of 5% with the N-gain of the experimental group is 0.35 and the control group is 0.04. Applying guided inquiry learning with outdoor activities setting is able to improve the psychomotor domain science process skills in the experimental group using the guided inquiry model with outdoor activities setting.